2021
DOI: 10.1039/d1cp00005e
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modelling solubility of amino acids and peptides in aqueous 2-propanol solutions

Abstract: Amino acids and peptides are essential components in the biochemical industry. The final products find use in a vast field of applications, are often synthesized by fermentation and purified in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Model correlation is important for the solubility data of solids. Many models have been reported to correlate or predict the solubility data of solids. In this work, the 5-FC solubility data is correlated by the famous modified Apelblat model, , λ h model, Jouyban–Acree model, , and CNIBS/R-K model …”
Section: Resultsmentioning
confidence: 99%
“…Model correlation is important for the solubility data of solids. Many models have been reported to correlate or predict the solubility data of solids. In this work, the 5-FC solubility data is correlated by the famous modified Apelblat model, , λ h model, Jouyban–Acree model, , and CNIBS/R-K model …”
Section: Resultsmentioning
confidence: 99%
“…Δ C p ( T m ) was applied in this work with the assumption on temperature independence of Δ C p . The activity coefficient of the solute in the solution was calculated by the PC-SAFT EoS, which has shown superior performance on the modeling solubility of drug-like molecules with medium sizes. , A fundamental description on the PC-SAFT can be found in the work of Gross and Sadowski . Due to the complexity of the PC-SAFT calculations, equation details on activity coefficients are not provided in this section to avoid distraction.…”
Section: Thermodynamic Modelsmentioning
confidence: 99%
“…8 Only 3 years later, Matsuo and Sawamura measured the solubility of L-leucine in water at 298.15 K. 9 After that, its solubility in water (298.15 K) was measured by Klussmann et al 10 Soon after, Bowden et al reported the ethanol solubility of L-leucine in 2018. 11 In addition, the solubility data in water and aqueous 2-propanol were determined by Do et al 12,13 Recently, the L-leucine solubility in water was measured by Aliyeva et al in 2022. 14 The mass fraction purity and the analysis methods were both provided by the suppliers.…”
Section: Introductionmentioning
confidence: 99%